Unraveling Diabetic Kidney Disease: The Roles of Mitochondrial Dysfunction and Immunometabolism - Phoom Narongkiatikhun; Ye Ji Choi; Hailey Hampson; Jimmy Gotzamanis; Guanshi Zhang; Daniel H. van Raalte; Ian H. de Boer; Robert G. Nelson; Kalie L. Tommerdahl; Phillip J. McCown; Jenny Kanter; Kumar Sharma; et al. (Kidney International Reports)
Mitochondria are essential for cellular energy production and are implicated in numerous diseases, including diabetic kidney disease (DKD). Current evidence indicates that mitochondrial dysfunction results in alterations in several metabolic pathways within kidney cells, thereby contributing to the progression of DKD. Furthermore, mitochondrial dysfunction can engender an inflammatory milieu, leading to the activation and recruitment of immune cells to the kidney tissue, potentially perturbing intrarenal metabolism. In addition, this inflammatory microenvironment has the potential to modify immune cell metabolism, which may further accentuate the immune-mediated kidney injury. This understanding has led to the emerging field of immunometabolism, which views DKD as not just a metabolic disorder caused by hyperglycemia but also one with significant immune contributions. Targeting mitochondrial function and immunometabolism may offer protective effects for the kidneys, complementing current therapies and potentially mitigating the risk of DKD progression. This comprehensive review examines the impact of mitochondrial dysfunction and the potential role of immunometabolism in DKD. We also discuss tools for investigating these mechanisms and propose avenues for integrating this research with existing therapies. These insights underscore the modulation of mitochondrial function and immunometabolism as a critical strategy for decelerating DKD progression.